A COMPARATIVE ANALYSIS ON NON-PERFORMING LOANS (NPLs) IN THE BANKING SECTORS OF BANGLADESH - Kumar Sarker, Sanjoy (International Journal of Research -GRANTHAALAYAH, 2019)
The aims of this study is to be analyzed the comparative position of all the fours banking categories on non-performing loans in Bangladesh and also investigate what are the different causes of non-performing loans in banking sectors of Bangladesh. This study will cover based on secondary data, which has been collected from the annual reports of the Bangladesh Bank during the 2006-2017 for 12 years and total NPL, NPL to Total Loans ratio and Trends of net NPL to total loans ratio are taken as variables of the study. The data are analyzed by using descriptive Statistics, ANOVA Test and the Test of Homogeneity of Variances. In this paper it is found that there is significant difference at the performances of four categories of banks on the Non-performing loans and there is no Homogeneity of Variances of total NPL, NPL to Total Loans ratio and Trends of net NPL to total loans ratio among all the banking categories. The SCBs and DFIs have continues maintain the high level of NPL and NPLs ratio to total loans then PCBs and FCBs and the NPLs recovery record during the study period has witnessed some sign or signal for improvement, due to number of step are taken with regard to internal restructuring for strengthen the loan recovery mechanism and initiative taken for written off measurement in recent time for all the banking categories. The suggestions and recommendation have been given for improve the present situation of non-performing loans in the banking sectors in Bangladesh.